Generation of an anticoagulant aptamer that targets factor V/Va and disrupts the FVa-membrane interaction in normal and COVID-19 patient samples. Issue 2 (17th February 2022) - Soule, Erin E.; Yu, Haixiang; Olson, Lyra; Naqvi, Ibtehaj; Kumar, Shekhar; Krishnaswamy, Sriram; Sullenger, Bruce A.
Summary: Coagulation cofactors profoundly regulate hemostasis and are appealing targets for anticoagulants. However, targeting such proteins has been challenging because they lack an active site. To address this, we isolate an RNA aptamer termed T18.3 that binds to both factor V (FV) and FVa with nanomolar affinity and demonstrates clinically relevant anticoagulant activity in both plasma and whole blood. The aptamer also shows synergy with low molecular weight heparin and delivers potent anticoagulation in plasma collected from patients with coronavirus disease 2019 (COVID-19). Moreover, the aptamer's anticoagulant activity can be rapidly and efficiently reversed using protamine sulfate, which potentially allows fine-tuning of aptamer's activity post-administration. We further show that the aptamer achieves its anticoagulant activity by abrogating FV/FVa interactions with phospholipid membranes. Our success in generating an anticoagulant aptamer targeting FV/Va demonstrates the feasibility of using cofactor-binding aptamers as therapeutic protein inhibitors and reveals an unconventional working mechanism of an aptamer by interrupting protein-membrane interactions. Graphical abstract: Highlights: Aptamers bind with low nanomolar affinity to coagulation cofactor FV/FVa Aptamers are potent anticoagulants in normal and COVID-19 plasma Protamine sulfate can rapidly reverse aptamer's anticoagulant activity Aptamers synergize with low molecular weight heparin (LMWH) Abstract : Coagulation cofactors are appealing yet challenging targets for anticoagulant development. Soule et al. describe a 2′F-modified RNA aptamer that potently inhibits coagulation cofactor FV/FVa docking to the cellular membrane and demonstrates clinically relevant anticoagulant activity in plasma and whole blood.